ANTICIPATORY GUIDANCE ORANGTUA UNTUK KEKERASAN SEKSUAL PADA ANAK (ANTICIPATORY GUIDANCE OF PARENTS FOR SEXUAL VIOLENCE IN CHILDREN) - Maria, Lilla; Handian, Feriana Ira; Rahmawati, Previta Zeisar (STIKes Maharani Malang, 2020)
Background: The violence problem against children is a complex problem that requires comprehensive, holistic and integrated treatment. Children are vulnerable groups both physically and fulfilment rights. Their existence depends on parent care and caregiver. Sometimes, their weakness used by other to commit violence. Violations can be identified physically, emotionally and sexually maltreatment. Objective: To formulate parent Anticipatory guidance for sexual violence against children through parent experience. Method: This study used a qualitative research with a phenomenological approach. Participants were parents whose children were victims or not of sexual violence, 5 participant were selected by purposive sampling in Malang district. Results: 1). The Government's Rapid Response Among the Dilemmas of Community Stigma, 2) Preventing Violence by Opening Discussion Room with Children, 3) Victim's Parents Hope Children be Able to Face the Future, 4). Involving Family and Environment in the Prevention of Sexual Violence in Children, 5). Rehabilitation of Victims of Sexual Violence in Children Considering the Victim's Condition. Conclusion: Anticipatory guidence of children associated with community stigma and the emergence feelings of shame. Openness communication and discussion with children and environmental involvement in supporting the prevention of sexual violence against children is very important to reduced the number of cases of sexual violence against children in the future.